Popular Culture and Intercultural Communication: The Voice and the Echo - Bakić Mirić, Nataša M.; Janković, Anita V.; Stojković, Nadežda M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The primary goal of popular culture as the dominant form of culture in the 21st century should be to unite people in a cultural synergy. Popular culture as such should insist on the richness of diversity, not on stereotypes, which is the case today. This paper will analyze the concepts of communication, culture, intercultural communication, cultural imperialism as well as the influence of popular culture on intercultural communication. Popular culture is a key component in creating a social identity in the 21st century. It provides a sense of belonging and togetherness to people around the globe. That is why they rely on popular culture to understand the world around them, and for most people, the view of the world exists only through the prism of popular culture.Although popular culture could be a hybrid space for bringing cultures closer, this is impossible today because the media deepens the gap between cultures with negative stereotypes by looking at other cultures through their own cultural prism. In order for cultures to come closer to one another, the media must be comprehensive in the way they present images in the broad category of meanings of the concepts of ‘culture’, ‘race’ and ‘nation’ so that people understand that culture exists on multiple levels of complexity, while popular culture presents a superficial (visible) part of culture based on which people mistakenly form a perception of a culture, which can be the cause of misunderstandings in intercultural communication.
Keywords: culture; communication; intercultural communication; popular culture; stereotypes; cultural imperialism